At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Let's solve the equation step-by-step:
The given equation is:
[tex]\[ 6y - 8 = 9y + 7 \][/tex]
Step 1: Isolate the variable [tex]\( y \)[/tex]. Start by moving all the [tex]\( y \)[/tex]-terms to one side and constant terms to the other side. Subtract [tex]\( 6y \)[/tex] from both sides:
[tex]\[ 6y - 8 - 6y = 9y + 7 - 6y \][/tex]
This simplifies to:
[tex]\[ -8 = 3y + 7 \][/tex]
Step 2: Next, isolate [tex]\( 3y \)[/tex] by subtracting 7 from both sides:
[tex]\[ -8 - 7 = 3y + 7 - 7 \][/tex]
This simplifies to:
[tex]\[ -15 = 3y \][/tex]
Step 3: Finally, solve for [tex]\( y \)[/tex] by dividing both sides by 3:
[tex]\[ y = \frac{-15}{3} \][/tex]
[tex]\[ y = -5 \][/tex]
So, the proposed solution is [tex]\( y = -5 \)[/tex].
Step 4: Verify the solution by substituting [tex]\( y = -5 \)[/tex] back into the original equation:
[tex]\[ 6y - 8 = 9y + 7 \][/tex]
Substitute [tex]\( y = -5 \)[/tex]:
[tex]\[ 6(-5) - 8 \stackrel{?}{=} 9(-5) + 7 \][/tex]
[tex]\[ -30 - 8 \stackrel{?}{=} -45 + 7 \][/tex]
[tex]\[ -38 = -38 \][/tex]
The left-hand side equals the right-hand side when [tex]\( y = -5 \)[/tex], so the solution [tex]\( y = -5 \)[/tex] checks out.
Therefore, the solution set is:
[tex]\[ \{-5\} \][/tex]
Hence, the correct choice is:
A. The solution set is \{-5\}.
The given equation is:
[tex]\[ 6y - 8 = 9y + 7 \][/tex]
Step 1: Isolate the variable [tex]\( y \)[/tex]. Start by moving all the [tex]\( y \)[/tex]-terms to one side and constant terms to the other side. Subtract [tex]\( 6y \)[/tex] from both sides:
[tex]\[ 6y - 8 - 6y = 9y + 7 - 6y \][/tex]
This simplifies to:
[tex]\[ -8 = 3y + 7 \][/tex]
Step 2: Next, isolate [tex]\( 3y \)[/tex] by subtracting 7 from both sides:
[tex]\[ -8 - 7 = 3y + 7 - 7 \][/tex]
This simplifies to:
[tex]\[ -15 = 3y \][/tex]
Step 3: Finally, solve for [tex]\( y \)[/tex] by dividing both sides by 3:
[tex]\[ y = \frac{-15}{3} \][/tex]
[tex]\[ y = -5 \][/tex]
So, the proposed solution is [tex]\( y = -5 \)[/tex].
Step 4: Verify the solution by substituting [tex]\( y = -5 \)[/tex] back into the original equation:
[tex]\[ 6y - 8 = 9y + 7 \][/tex]
Substitute [tex]\( y = -5 \)[/tex]:
[tex]\[ 6(-5) - 8 \stackrel{?}{=} 9(-5) + 7 \][/tex]
[tex]\[ -30 - 8 \stackrel{?}{=} -45 + 7 \][/tex]
[tex]\[ -38 = -38 \][/tex]
The left-hand side equals the right-hand side when [tex]\( y = -5 \)[/tex], so the solution [tex]\( y = -5 \)[/tex] checks out.
Therefore, the solution set is:
[tex]\[ \{-5\} \][/tex]
Hence, the correct choice is:
A. The solution set is \{-5\}.
Answer:
hello
Step-by-step explanation:
6y-8=9y+7
6y-9y-8=9y-9y+7
-3y-8+8=7+8
-3y=15
(-3y)/-3=15/-3
y=-5
The solution set is : -5
Verification:
6*-5-8=9*-5+7
-30-8=-45+7
-38=-38
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.